(untitled) (The Research of Medical Science Review, 2025)
Objective: This study aimed to determine the frequency of clinical manifestations of typhoid fever in children aged 2 to 12 years and compare the clinical spectrum between vaccinated and non-vaccinated children. Methodology: The study was a cross-sectional study done in Pediatric Medicine Department, Liaquat University Hospital, Hyderabad/Jamshoro on October 21, 2023, to April 20, 2024. One hundred and thirteen (113) children aged between 2 years and 12 years who had proven blood culture-confirmed typhoid fever were recruited. Vaccination was evaluated by use of recall phenomenon or immunizations cards. A structured proforma was used to collect data on demographic characteristics as well as clinical symptoms. Results: The age of participants varied and was median as 5 (IQR: 38) with only a slight majority of males (54.0). The most frequent was the symptom of fever (99.1%), then diarrhea (35.4%), abdominal pain (32.7%), headache (26.5%), and constipation (13.3%). There were no substantial differences between vaccinated and non-vaccinated children on clinical spectrum of any symptom (p > 0.05). Conclusion: The clinical profile of typhoid fever in children with the age 2-12 years is also reliable irrespective of the use of Typbar-TCV vaccine. At the same time, vaccination can help prevent the disease but does not have a huge impact on the breakthrough cases symptomatology. Such results underline an increased need to enhance diagnostics, further healthcare immunization, and enhance the mitigation of the public health activities. Future research aimed at investigating the effect of vaccines on severity upon acquiring the disease and long-term results should be conducted.